Confining Nitrogen Inversion to Yield Enantiopure Quinolino[3, 2, 1‐k]Phenothiazine Derivatives. (1st August 2018) - Quinton, Cassandre; Sicard, Lambert; Vanthuyne, Nicolas; Jeannin, Olivier; Poriel, Cyril
Abstract: The first examples of optically pure 9H‐quinolino[3, 2, 1‐k]phenothiazine (QPTZ)‐based molecules are reported. The inversion of the nitrogen atom, locked in the QPTZ fragment, is confined with a high‐energy barrier that has allowed the isolation at room temperature of each stereoisomer. Considering the growing necessity in molecular electronics to introduce chiral characteristics within highly efficient molecular fragments, a molecular strategy to generate enantiopure derivatives constructed on the very promising electron rich core QPTZ is provided. As this work aims to report the foundations of the QPTZ chirality, the present findings may open avenues towards the use of this fragment in its optically pure form. Abstract : Thanks to a complete (both experimental and theoretical) study of the nitrogen inversion in fluorene‐ spiro ‐quinolinophenothiazine derivatives, guidelines are provided for the use of the quinolinophenothiazine functional unit as a chiral fragment within electronic devices.